The use of antimicrobial agents in broiler chickens - Landoni, Maria Fabiana (2015)
Abstract: Antimicrobial agents are essential tools for treating and controlling bacterial infections in poultry production. Veterinarians have a huge responsibility when using antimicrobials in poultry producing meat and eggs for human consumption. ´Judicious use´ of antimicrobials implies the optimal selection of drug, dose and duration of antimicrobial treatment, along with a reduction in the inappropriate and excessive use as a means of slowing the emergence of antimicrobial resistance. The proper use of these drugs depends on the knowledge of bacteria/antimicrobial/host/consumer interrelationships. This article reviews anatomo-physiological features of poultry related to drug disposition as well as pharmacological and therapeutic characteristics of the most commonly used antimicrobials in broiler chickens. Commonly used doses for flock treatment are presented as well as accepted withdrawal times.